A systematic review of the cost and cost-effectiveness of electronic discharge communications. Issue 6 (2nd July 2017) - Sevick, Laura K; Esmail, Rosmin; Tang, Karen; Lorenzetti, Diane L; Ronksley, Paul; James, Matthew; Santana, Maria; Ghali, William A; Clement, Fiona
Abstract : Background: The transition between acute care and community care can be a vulnerable period in a patients' treatment due to the potential for postdischarge adverse events. The vulnerability of this period has been attributed to factors related to the miscommunication between hospital-based and community-based physicians. Electronic discharge communication has been proposed as one solution to bridge this communication gap. Prior to widespread implementation of these tools, the costs and benefits should be considered. Objective: To establish the cost and cost-effectiveness of electronic discharge communications compared with traditional discharge systems for individuals who have completed care with one provider and are transitioning care to a new provider. Methods: We conducted a systematic review of the published literature, using best practices, to identify economic evaluations/cost analyses of electronic discharge communication tools. Inclusion criteria were: (1) economic analysis and (2) electronic discharge communication tool as the intervention. Quality of each article was assessed, and data were summarised using a component-based analysis. Results: One thousand unique abstracts were identified, and 57 full-text articles were assessed for eligibility. Four studies met final inclusion criteria. These studies varied in their primary objectives, methodology, costs reported and outcomes. All of the studies were of low to good quality. Three of the studies reported a cost-effectiveness measure ranging from an incremental daily cost of decreasing average discharge note completion by 1 day of 0.331 (2003 Canadian), a cost per page per discharge letter of €9.51 and a dynamic net present value of €31.1 million for a 5-year implementation of the intervention. None of the identified studies considered clinically meaningful patient or quality outcomes. Discussion: Economic analyses of electronic discharge communications are scarcely reported, and with inconsistent methodology and outcomes. Further studies are needed to understand the cost-effectiveness and value for patient care.